Variations of pest and disease attacks on horticultural and non-horticultural crops in South Sumatra - Arsi Arsi; Bambang Gunawan; Suparman Suparman; Titi Tricahyati; Hesti Hesti (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
Horticultural crops of olericultural types that were given a lot of chemical pesticides cause many negative impacts such as the emergence of pests and pathogens that were immune to pesticides, the emergence of new pests, increased pest populations and secondary pathogens, reduced populations of beneficial insects (predators). The study aimed to consider the use of pesticides by farmers to eradicate pests and diseases in horticulture and non-horticulture in South Sumatra. The research was conducted in South Sumatra Province. The research was conducted in 7 districts and 1 city, namely Indralaya District, North Indralaya District, Air Kumbang District, South Pemulutan District, Gelumbang District, Belitang Mulya District, Tanjung Batu District, and Palembang City, which was conducted from May to September 2022. Data were collected using the Secondary Variables method with Purposive sampling technique and processed into analyzed data. The results of this study showed that the most horticulture cultivated by farmers was eggplant(Solanum melongena L.). While for non-horticulture the most widely cultivated by farmers was corn(Zea mays). The percentage of pest attacks on non-horticultural land was 57.36%, the percentage of pest attacks on horticultural land was 68.28%. Variations in pest and disease attacks that occur in 180 farms on horticultural and non-horticultural crops in South Sumatra. Horticultural crops that are widely cultivated in South Sumatra include cucumber, long beans, and eggplant. Meanwhile, non-horticultural crops are corn, rice, and rubber. Spodoptera frugiperda was a pest that has been found to damage corn crops and Leptocorisa sp species that damage food crops (No Horticulture). Counseling was provided to farmers to find out the types of pests that could attack and the symptoms and diseases in plants to know how to control them.